A 0.15μ Vrms super-sensitivity photoacoustic imager based on coherent detection for deep in-vivo imaging - Yang, Chuanshi (2023)
Among various multi-wave imaging methods, the photoacoustic imaging (PAI) has attracted more attention because it can achieve higher resolution and contrast through combining advantages of light excitation and ultrasound detection. However, due to low restricted laser fluence, large scattering and attenuation in tissue, and low energy conversion efficiency, high sensitivity is still imperative in the receiver to read out PA signals. A new photoacoustic receiver with mixed-signal coherent detection technique is developed and fabricated for the first time. Co-working with the early-late acquisition and tracking technique, the receiver can lock into the weak PA signal automatically. For the receiver system on chip (SoC), a high performance analog front-end (AFE) with a low noise amplifier (LNA), low-pass filter (LPF), programmable-gain amplifier (PGA), multiplier, successive-approximation analog-to-digital converter (SAR ADC) and digital-to-analog converter (DAC) are implemented on chip. Noise shaping (NS) technique is implemented in the SAR ADC to enhance the signal-to-noise ratio (SNR). Measurement results show that, the LNA achieves 0.23mPa√(mW/Hz) noise efficiency factor (NEF) with the aid of resonant noise matching (RNM) technique, and the NS-SAR ADC can obtain 62.2dB signal-to-noise-and-distortion ratio (SNDR) in 10MHz bandwidth under 100MS/s sampling rate. The single channel receiver can achieve 135dB dynamic range and 0.15μ Vrms sensitivity. The output SNR can be improved by about 6dB after enabling the 4 channels. The power consumption of a single channel is 28.8mW. The contrast-to-noise ratio (CNR) of the images at 1cm depth is 44dB.